PEMBELAJARAN DARING PERSPEKTIF GENDER MALALUI MODEL RASCH - Indah Wigati (Universitas Muhammadiyah Ponorogo, 2021)
Advances in computer technology, especially the internet, are currently very influential on all aspects of life, including education. Technological advances in education present a distance learning process online using the internet. This has resulted in increased demands for teachers in teaching which are not only focused on mastering the material, but must be supported by the application and mastery of IT that supports knowledge for exploration and creation of independent learning. In practice, the implementation of this learning has advantages and disadvantages. This is related to the readiness of internet facilities, teachers, and students. The purpose of this study was to test the online learning system for students of the Teacher Professional Program (PPG) with a gender perspective at FITK UIN Raden Fatah Palembang. The research method used is quantitative. Data analysis used Rasch analysis and Gender Analysis Pathway (GAP). The results showed that student responses to the use of the online web were categorized into 2 groups of persons, namely respondents as the high group and the medium group. There are 69 people in the high group category and 47 people in the moderate group with a balanced distribution of the number of men and women. The conclusions of the study stated that the use of the online learning system for PPG students did not show a statistically significant difference between men and women.